Peran Pendidikan Agama Islam Dalam Menanamkan Nilai Anti Korupsi Pada Generasi Muda Di Era Digital - Eli Sabrifha; Nabila Salsa (CV. SINAR HOWUHOWU, 2026)
Corruption is a serious problem threatening the life of the nation and state in Indonesia. Amid the rapid development of the digital era, the challenges of instilling anti-corruption values in the younger generation are increasingly complex. Islamic Religious Education (PAI) as one of the compulsory subjects in schools has great potential in building anti-corruption character through the internalization of values of honesty, responsibility, and trustworthiness sourced from Islamic teachings. This research uses a qualitative approach with a literature review method to examine the strategic role of PAI in instilling anti-corruption values in the younger generation in the digital era. The results of the study indicate that PAI can be an effective instrument in forming anti-corruption character through an integrative approach that combines digital technology-based learning with the strengthening of Islamic values. Synergy is needed between educators, educational institutions, families, and the government to create a young generation with integrity and free from corruption.